2020
DOI: 10.1002/qua.26217
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alloying elements on the mechanical and thermodynamic properties of ZrB12ceramics from first‐principles calculations

Abstract: Although ZrB 12 is a promising advanced material because of the boron cuboctahedron cages, the hardness of ZrB 12 remains controversy. Here, we apply first-principles calculations to study the influence of transition metals (4d-and 5d-) on the hardness and thermodynamic properties of ZrB 12 . The calculated hardness of ZrB 12 is 32.9 GPa, which is in good agreement with the previous theoretical result. Importantly, the calculated hardness of Re-doped ZrB 12 is up to 40.0 GPa, which is a potential superhard mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 82 publications
0
10
1
Order By: Relevance
“…The relatively small value of σ (0.151) suggests the strong covalent bonds in Zr 0.5 Y 0.5 B 12 . The intrinsic Vickers hardness of Zr 0.5 Y 0.5 B 12 is larger than the previously reported results of ZrB 12 (~32.9 GPa [12] and 33.6 GPa [22]), which is attributed the change of localized hybridization between B and Zr atoms due to the Y doping [12]. The difference of Vickers hardness between our calculation and experimental result (45.8 GPa) [3] maybe result from the effects of sample morphology, microstructure and other minor precipitated phases, et al The fracture toughness is 3.067 MPaÁm 0.5 , approaching the value of 3.12 MPaÁm 0.5 of α-Si 3 N 4 [23], and smaller than that of diamond 5-7 MPaÁm 0.5 [19].…”
Section: Equilibrium Structure and Elastic Propertiescontrasting
confidence: 71%
See 2 more Smart Citations
“…The relatively small value of σ (0.151) suggests the strong covalent bonds in Zr 0.5 Y 0.5 B 12 . The intrinsic Vickers hardness of Zr 0.5 Y 0.5 B 12 is larger than the previously reported results of ZrB 12 (~32.9 GPa [12] and 33.6 GPa [22]), which is attributed the change of localized hybridization between B and Zr atoms due to the Y doping [12]. The difference of Vickers hardness between our calculation and experimental result (45.8 GPa) [3] maybe result from the effects of sample morphology, microstructure and other minor precipitated phases, et al The fracture toughness is 3.067 MPaÁm 0.5 , approaching the value of 3.12 MPaÁm 0.5 of α-Si 3 N 4 [23], and smaller than that of diamond 5-7 MPaÁm 0.5 [19].…”
Section: Equilibrium Structure and Elastic Propertiescontrasting
confidence: 71%
“…Alloying is an effective method to enhance the Vickers hardness of materials. The effects of alloying elements (Nb, Mo, W, Re, and Os) on the hardness and thermodynamic properties of ZrB 12 were investigated using the first-principles calculation [12]. They deemed that the alloying elements improved the localized hybridization between B and Zr atoms, which increased the Vickers hardness [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is concluded that the five novel monoclinic stable TMAl 3 aluminides: ScAl 3 , TiAl 3 , VAl 3 , CrAl 3 , and WAl 3 are first predicted. To study the mechanical properties, it is studied the elastic properties and intrinsic hardness (H v ) [55][56][57][58] of TMAl 3 . Here, the elastic properties of a solid have four key parameters: bulk modulus (B), shear modulus (G), Young's modulus (E), and Poisson ratio (σ) [59,60].…”
Section: Resultsmentioning
confidence: 99%
“…Both experimental and theoretical results were in good agreement. In Reference [ 15 ], however, the mechanical properties of ZrB were calculated. The Vickers hardness of zirconium boride was 32.9 GPa, which is in good agreement with other theoretical results [ 14 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%